Knee pain in children. Issue 12 (December 2019) - Ng, Jimmy Wui Guan; Price, Kathryn; Deepak, Samundeeswari
Abstract: Knee pain is common in children, particular during adolescence. A detailed history and clinical examination often will identify the likely cause. Health care professionals looking after children and young people should be aware of the common causes of knee pain and red flags which are a feature of more sinister causes. Common causes of knee pain include patellofemoral problems, apophysitis such as Osgood Schlatter's disease and Sinding-Larsen-Johansson Syndrome, osteochondritis dissecans, trauma, rheumatological causes such as juvenile idiopathic arthritis, and infective causes as such septic arthritis and osteomyelitis. Malignancy must be excluded when there are red flag signs. Non-accidental injury and referred pain from the hip if not considered, can be easily missed. This review offers practical advice regarding the assessment of knee pain.